Interpreting Islam - Donnan, Hastings (Politics and culture (London, England), 2002)
Surrounded by myths and stereotypes, Islam is one of the least understood religions in the West. Interpreting Islam provides a penetrating guide to the diversity and richness of contemporary knowledge about Islam and Muslim society in general.